Explaining China's Mediation in Middle East Conflicts:Based on the conceptual model of Jacob Berkovich (Syrian crisis ) - enayat yazdani; bahar akhavan (رهیافتهای سیاسی و بین المللی)
In the days when the emergence of China as a major power has affected the modern world order. China pursues its economic and political opportunities in a multi-dimensional approach in the Middle East as a center of strength and wealth. One of the areas Beijing has placed on its agenda in the Middle East is the effective presence as a mediator in resolving regional disputes. The study intends to analyze China's mediation behavior based on Jacob Berkovich's "probabilistic" theory and poses the question of how likely the success of China mediation is based on this theory. In response to this question, this hypothesis has proven that, based on the conceptual model of Brevkov, it seems that China's mediation in Middle Eastern conflicts, based on China's emerging power, is based on the most successful "mediation" strategy And the most active form of mediation is measurable. Beijing has had an indisputable indicator of the Middle East conflict resolution of the recent Syrian crisis, which has enabled the country to influence the parties to the conflict with great power. Given China's differing approaches to resolving conflicts as a mediator of this global power, with the transformation of polarization, it intends to establish a normative approach and a unique peaceful Middle East value that parallels multilateral partners through stabilization. Emphasizing political solutions and expanding negotiations, instead of using force and military power to resolve conflicts in the region.